How to do everything : Microsoft SharePoint 2010 - Cawood, Stephen (New York : McGraw-Hill, 2010)
Explains how to get the most out of this powerful business collaboration platform. Learn how to use document management functions, wikis, taxonomy, blogs, My Sites, web parts, and more. Take full advantage of the content management, enterprise search, collaboration, and information-sharing capabilities of SharePoint 2010 with help from this practical guide.
Introduction -- SharePoint concepts -- Document management -- Collaboration -- Taxonomy -- Search -- Navigation -- MySites -- Web parts -- Customization -- SharePoint Workspace -- SharePoint training resources -- SharePoint best practice resources.
Includes index.
Keywords: Microsoft Office; Microsoft SharePoint (Electronic resource); Business -- Computer programs; Intranets (Computer networks)